Radiographic Evaluation of Posterior Tibial Slope Angle: Its Relationship with Socio-Demographic Factors and Effects on Knee Function (Nigerian Journal of Physiological Sciences, 2025)
Major activities in life depend on the proper function of the knees which in turn is determined by the posterior tibial slope angle (PTSA) of the knee. However, beyond certain degrees of PTSA the likelihood of the risk for tears in the anterior cruciate ligament (ACL), posterior cruciate ligament (PCL) and menisci increases, which consequently, impairs knee joint functions. The objectives of this study were to determine PTSA, its relationship with sociodemographic factors and effect on subjective knee joint function using Tegner activity scale. This was a prospective cross-sectional observational study that was conducted in the Radiology Department of a Tertiary hospital over a 6-moths period. PTSA of the lateral radiographs of 152 subjects were evaluated. Tegner activity scale was administered on each subject to subjectively ascertain knee joint function. Chi square and Pearson’s correlation were used to analyze the data. Mean PTSA for the right and left knees were 11.03±0.250 (SEM) and 11.02±0.260 (SEM). Age and body mass index (BMI) significantly correlated with right PTSA (r = 0.404, P = 0.000 and r = -0.853, P = 0.000) and left PTSA (r = 0.408, P = and r = -0.818, P = 0.000). Mean Tegner activity scale was 8.47±0.38 (SEM) and the mean BMI was 24.06±0.29 kg/m2 (SEM). It is concluded that mean PTSA in this study is similar to that obtained in other populations and has a significant relationship with age and BMI, and maintaining normal weight significantly affects PTSA in a positive fashion to ensure optimal knee functions. This study offers regional data to assist Orthopaedic surgeons on knee ligaments evaluation and reconstruction procedures.